2020
DOI: 10.1002/ncp.10551
|View full text |Cite
|
Sign up to set email alerts
|

Feeding Disorders in Children With Tracheostomy Tubes

Abstract: Background We aimed to describe feeding dysfunction in a group of children with tracheostomy. Methods Single‐center, retrospective chart review of all children with a tracheostomy who were evaluated by our interdisciplinary feeding program. Demographic and diagnostic data, nutrition variables, acceptance of food consistencies, as well as 2 validated psychometric instruments for assessment of feeding dysfunction were analyzed. Results Thirteen tracheostomy‐dependent children (5/13; 38% ventilator dependent) wer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
6
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 28 publications
0
6
0
1
Order By: Relevance
“…Another study looked at 5‐year outcomes of children with IMV and identified a high association between neurocognitive function and ventilator dependence, although cognitive assessment was determined by chart review and team consensus, without objective measures 17 . Mechanistically, it is thought that prolonged oral intubation and the presence of a tracheostomy may limit essential early speech and feeding opportunities, and increase likelihood of feeding problems and impaired oral motor skills underlying language expression 18–20 …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Another study looked at 5‐year outcomes of children with IMV and identified a high association between neurocognitive function and ventilator dependence, although cognitive assessment was determined by chart review and team consensus, without objective measures 17 . Mechanistically, it is thought that prolonged oral intubation and the presence of a tracheostomy may limit essential early speech and feeding opportunities, and increase likelihood of feeding problems and impaired oral motor skills underlying language expression 18–20 …”
Section: Introductionmentioning
confidence: 99%
“…17 Mechanistically, it is thought that prolonged oral intubation and the presence of a tracheostomy may limit essential early speech and feeding opportunities, and increase likelihood of feeding problems and impaired oral motor skills underlying language expression. [18][19][20] As a whole, the developmental outcomes of children with IMV have been studied within larger premature cohorts, and have shown greater risk for developmental delays than other prematurely born infants. However, the extent of these delays, their distribution, trajectories, and protective or confounding influence across diverse populations are yet unknown.…”
mentioning
confidence: 99%
“…The rates of PFD are higher in children with other chronic diseases like short bowel syndrome and children with tracheostomy (20,21). Overall, PFD criteria were met by nearly 2 out of 3 children with CF in our study.…”
Section: Discussionmentioning
confidence: 99%
“…Our own group has studied PFD in 3 chronic conditions: in children with tracheostomy (20), short bowel syndrome (21), and in the current study, CF. In each of these, the hypothesis was different.…”
Section: Discussionmentioning
confidence: 99%
“…Little is known about the specific mealtime behaviors of children who are tube fed with the goal of transitioning to oral feeding. The most commonly used method to assess mealtimes is parent report obtained via questionnaires or interview (Ax et al, 2020; Henningfeld, 2020). While several questionnaires and interviews demonstrate adequate sensitivity and validity, others lack generalizability among multiple childhood illnesses or developmental sub-groups (for a listing of specific strengths and weaknesses, see Poppert et al, 2015).…”
Section: Introductionmentioning
confidence: 99%